2019
DOI: 10.1002/jso.25637
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative dynamic survival of gastric cancer patients: A multi‐institutional, international analysis of 22 265 patients

Abstract: Background: How to best evaluate the disease-specific survival (DSS) of gastric cancer (GC) survivors over time is unclear.Methods: Clinicopathological data from 22 265 patients who underwent curative intend resection for GC were retrospectively analyzed. Changes in the patients'3-year conditional disease-specific survival (CS3) were analyzed. We used timedependent Cox regression to analyze which variables had long-term effects on DSS and devised a dynamic predictive model based on the length of survival.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…The most important issue is ensuring proper oncological surgery by performing an adequate lymphadenectomy with minimally invasive approaches. Researchers still regard nodal clearance as an important factor in uencing long-term survival [6][7][8][9][10][11][12][13]. In randomized trials [3], laparoscopy demonstrated the removal of at least 15 lymph nodes, as required by international guidelines [14]; however, a signi cant difference in favor of open surgery resulted in the total number of lymph nodes harvested.…”
Section: Introductionmentioning
confidence: 99%
“…The most important issue is ensuring proper oncological surgery by performing an adequate lymphadenectomy with minimally invasive approaches. Researchers still regard nodal clearance as an important factor in uencing long-term survival [6][7][8][9][10][11][12][13]. In randomized trials [3], laparoscopy demonstrated the removal of at least 15 lymph nodes, as required by international guidelines [14]; however, a signi cant difference in favor of open surgery resulted in the total number of lymph nodes harvested.…”
Section: Introductionmentioning
confidence: 99%